Lack of Visual Orienting to Biological Motion and Audiovisual Synchrony in 3-Year-Olds with Autism - Falck-Ytter, T.; Rehnberg, E.; Bölte, Sven (Public Library of Science, 2013)
It has been suggested that children with autism orient towards audiovisual synchrony (AVS) rather than biological motion and that the opposite pattern is to be expected in typical development. Here, we challenge this notion by showing that 3-year-old neurotypical children orient to AVS and to biological motion in point-light displays but that 3-year-old children with autism orient to neither of these types of information. Thus, our data suggest that two fundamental mechanisms are disrupted in young children with autism: one that supports orienting towards others' movements and one that supports orienting towards multimodally specified events. These impairments may have consequences for socio-cognitive development and brain organization.